2015
DOI: 10.1007/s10856-014-5333-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biological evaluation of lignin addition to simple and silver-doped hydroxyapatite thin films synthesized by matrix-assisted pulsed laser evaporation

Abstract: We report on thin film deposition by matrix-assisted pulsed laser evaporation of simple hydroxyapatite (HA) or silver (Ag) doped HA combined with the natural biopolymer organosolv lignin (Lig) (Ag:HA-Lig). Solid cryogenic target of aqueous dispersions of Ag:HA-Lig composite and its counterpart without silver (HA-Lig) were prepared for evaporation using a KrF* excimer laser source. The expulsed material was assembled onto TiO2/Ti substrata or silicon wafers and subjected to physical-chemical investigations. Smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 47 publications
1
38
0
2
Order By: Relevance
“…Pathogens found at infected oral implant sites, including S. mutans 90) , S. aureus 93,94) , S. oralis 43) , P. gingivalis and A. actinomycetemcomitans 84) were killed or significantly reduced upon contact with silver-implanted surfaces. All tested silver surfaces, such as hydroxyapatite (HA)-silver-surfaces 42,44,[46][47][48][49][50][51]91,161) or plasma sprayed silver-implanted HA 45,95) shared good antimicrobial activity.…”
Section: Silver-implanted Surfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathogens found at infected oral implant sites, including S. mutans 90) , S. aureus 93,94) , S. oralis 43) , P. gingivalis and A. actinomycetemcomitans 84) were killed or significantly reduced upon contact with silver-implanted surfaces. All tested silver surfaces, such as hydroxyapatite (HA)-silver-surfaces 42,44,[46][47][48][49][50][51]91,161) or plasma sprayed silver-implanted HA 45,95) shared good antimicrobial activity.…”
Section: Silver-implanted Surfacesmentioning
confidence: 99%
“…Dextran and polyethylene glycol (PEG) surfaces have been shown to be effective in suppressing protein adhesion, platelet adhesion, bacterial adhesion and biofilm formation of oral relevant pathogens, such as S. aureus, S. sanguinis, L. salivarius S. mutans and S.gordonii 29,96,[101][102][103]107) . Lignin, a complex, amorphous organic polymer found in plant tissues, exhibits antibacterial activity against S. aureus, P. aeruginosa and C. famata 51) . Polypyrrole-coated titanium surfaces exhibit a three-fold greater repellent effect than a common TiAl 6V alloy against E.coli and S. aureus 104) .…”
Section: Polymeric Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds were solubilized in DMSO to a final concentration of 10 mg/mL and further sterilized by filtration (using 0.22 µm filter membranes). The quantitative assay of the minimal inhibitory concentration (MIC, µg/mL) was performed by the microdilution method in 96 multi-well plates [59]. In this purpose, serial binary dilutions (ranging between 1024 and 8 µg/mL) were achieved in nutrient broth/YPG (yeast peptone glucose) and each well was seeded with microbial inoculum of 0.5 McFarland density.…”
Section: In Vitro Assessment Of the Antimicrobial Activity Of The Newmentioning
confidence: 99%
“…Until now, biocomposite coatings based on the renewable lignin were studied by electrophoretic deposition (EPD) only [36,37], and the results revealed that the obtained composite exhibited enhanced stability and improved interconnected structure, with an increased coating cohesion [53]. For electrophoretic deposition (EPD) method, it was applied a constant voltage (at optimized parameters 60 V for 45 s), and it were obtained uniform composite coatings with good adhesion and mechanical properties without any phase transformation [67].…”
Section: Case Study: Lignin-based Biocompositesmentioning
confidence: 99%